The Learning Model of Happiness through French Literature Appreciation - Syaefudin, Mohamad; Emzir, Emzir; Lustyantie, Ninuk (Language Circle: Journal of Language and Literature, 2018)
his study aims to (1) develop learning models of happiness in learning French through literary works, and (2) to describe the application of learning models of happiness in learning French through literary works. The study applied a qualitative approach with two designs in exploratory research (1) to produce a learning model of happiness and (2) action research to evaluate the implementation of the learning model in the field. Data collection techniques are conducted through (1) in-depth interviews with French experts, (2) literary experts; and (3) psychologists to gain an important point of learning happiness. Then from the results of in-depth interview was compiled draft learning model of happiness through focus group discussion This research was conducted at Universitas Negeri Semarang, with research time from March to October 2017.The results of this research are the model of happiness teaching with ASSURE model which includes analyzing the students, formulating specific learning objectives, choosing methods, media, and teaching materials, utilizing media and teaching materials, requesting student response, and evaluation.